Analisis Opini Auditor Sebagai Sinyal Kepailitan Suatu Perusahaan: Tinjauan Terhadap Perlunya Kode Etik Syariah Akuntan Publik - Sugiyarti Fatma Laela; Dewi Lestari Meikhati (Institute for Research and Community Empowerment (LPPM TAZKIA), 2009)
Auditor is a professional who has credibility in auditing financial report and company’s activities. This research’s purpose is to figure out; does the company’s bankruptcy can be predicted from the auditor’s opinion. The data used in this research are taken from 33 companies which have announced to bankruptcy by state justice of Central Jakarta, and the recent three years auditor’s opinions before the companies’ bankruptcy. After the data have been analyzed with T-test and Friedman test, it goes to the result that there is no significant different between the whole auditor’s opinions in last three years before the companies’ bankruptcy. This research concludes that the bankruptcy cannot be predicted from the auditor’s opinion. Theoretically, the auditor’s opinion can be a tool in predicting the company’s bankruptcy. The deviation of auditor’s ethical codes causes to such this matter happen. Based on that fact, the shariah based ethical codes for auditor is needed. After deep learning from many literatures, the writer formulates shariah ethical codes for auditor which divides into two; relationship between Allah and Human, it performed with the faith (Iman), and the other one is relationship among all humans, it involves the objectivity, independency, professionalism, and integrity.JEL Classification : M40, M42Keywords : auditor, auditor’s opinion, Islamic auditor’s ethical codes